2014
DOI: 10.1007/s13277-014-2399-6
|View full text |Cite
|
Sign up to set email alerts
|

The Axin2 rs2240308 polymorphism and susceptibility to lung cancer in a Chinese population

Abstract: Axis inhibition protein 2 (Axin2) is a negative regulator of the canonical Wnt/β-catenin signaling pathway, and functions as a tumor suppressor in a number of human cancers. Previous pilot studies have suggested an association between Axin2 exon1 148 (rs2240308) SNP polymorphism and risk for lung cancer. In the present study, we aimed to investigate the Axin2 exon1 148 polymorphism and its association with lung cancer susceptibility in Han Chinese population. The Axin2 exon1 148 SNP was genotyped in 555 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…21 It was keen to observe a protective effect in subjects who carried the variant (TT) genotype for Axin2 148 C > T (p = 0.01). Many studies have evidently reported the same 20 The similar results have been reported in Chinese 23 and Japanese lung cancer patients. 21 Also, similar reports are available in case of other type of cancers including breast, 33 prostate, 24 astrocytoma, 25 and ovarian.…”
Section: Cart Analysissupporting
confidence: 67%
“…21 It was keen to observe a protective effect in subjects who carried the variant (TT) genotype for Axin2 148 C > T (p = 0.01). Many studies have evidently reported the same 20 The similar results have been reported in Chinese 23 and Japanese lung cancer patients. 21 Also, similar reports are available in case of other type of cancers including breast, 33 prostate, 24 astrocytoma, 25 and ovarian.…”
Section: Cart Analysissupporting
confidence: 67%
“…Thus, this diminished sensitivity of axin2 for inhibition by upstream signalling provides an elegant explanation for the effective restoration of destruction complex activity by axin2 (Bernkopf et al, ). The importance of axin2‐mediated feedback is further illustrated by the clear association between axin2 germline variants with increased cancer risk (Liu et al, ; Aristizabal‐Pachon et al, ; Rosales‐Reynoso et al, ; Bahl et al, ) and the occurrence of somatic axin2 frameshift mutations in various types of cancer (Mazzoni and Fearon, ; Li et al, ).…”
Section: Axin2/conductin‐mediated Feedback Promotes β‐Catenin Destrucmentioning
confidence: 99%
“…However, previous reports on the association between the AXIN2 rs2240308 polymorphism and risk of cancer show inconsistent results. Thus, significant associations were found with lung, prostate, and breast cancer (Gunes et al, 2009;Liu et al, 2014;Ma et al, 2014;Aristizabal-Pachon et al, 2015), but not with astrocytoma , ovarian cancer (Mostowska et al, 2014), head and neck cancer, and CRC (Kanzaki et al, 2006;Naghibalhossaini et al, 2012). Ethnic differences have also been observed in the association between the AXIN2 rs2240308 polymorphism and cancer risk Gong et al, 2015;Wu et al, 2015;Zhong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%